Family adjustment in workers of different company sizes and economic activities - Reyes-Romero, Carlos (2024)
Family maladjustment was investigated in workers from three company sizes, micro, small and medium, and from different economic sectors in Metropolitan Lima, using a descriptive-comparative design. The results allowed us to corroborate the hypothesis of family maladjustment with a proportion of around 30% at a high level. Likewise, although they were found to be significant between company types, the effect size was almost non-existent. The results are discussed under the ecological model of development, as well as the probable incidence of post-pandemic events and the social problems of current Peru.